2009
DOI: 10.1183/09031936.00122607
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea and its association with gestational hypertension

Abstract: Hypertension develops in 10% of pregnancies. Snoring, a marker of obstructive sleep apnoea, is a newly identified risk factor for gestational hypertension. Moreover, obstructive sleep apnoea is an independent risk factor for incident hypertension in the non-pregnant population. The aim of the present study was to test the hypothesis that obstructive sleep apnoea is associated with new onset of hypertension among pregnant females.A case-control study was performed involving 17 pregnant females with gestational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 29 publications
5
85
1
Order By: Relevance
“…Snoring could be indicative of flow limitation, for instance, which would not meet criteria for apnoea or hypopnoea. A recent study has found a significantly elevated apnoea/hypopnoea index, with hypopnoeas defined as a flow limitation without desaturation in females with gestational hypertension; however, the study did not evaluate the association of these findings with symptoms of SDB [29]. Evidence evaluating the association of symptoms of SDB with polysomnographic evidence of SDB in pregnancy is lacking.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Snoring could be indicative of flow limitation, for instance, which would not meet criteria for apnoea or hypopnoea. A recent study has found a significantly elevated apnoea/hypopnoea index, with hypopnoeas defined as a flow limitation without desaturation in females with gestational hypertension; however, the study did not evaluate the association of these findings with symptoms of SDB [29]. Evidence evaluating the association of symptoms of SDB with polysomnographic evidence of SDB in pregnancy is lacking.…”
Section: Discussionmentioning
confidence: 92%
“…A small number of studies have evaluated the association between SDB symptoms and fetal outcomes [14,17,29,47] and are somewhat conflicting [14,17] with some lacking a control arm [29]. A large study has shown an association between snoring and fetal growth restriction [14].…”
Section: Neonatal Outcomesmentioning
confidence: 99%
“…Diagnostic polysomnography was performed as previously described either in the sleep laboratory (Sandman; Tyco Inc., Ottawa, Canada) [4] or at home (Suzanne portable complete polysomnography device; Tyco Inc.) [22]. The same signals were recorded during both types of studies and analysis was performed on the same computerised system (Sandman version 6.2) using identical scoring criteria.…”
Section: Polysomnographymentioning
confidence: 99%
“…The same signals were recorded during both types of studies and analysis was performed on the same computerised system (Sandman version 6.2) using identical scoring criteria. Polysomnographic recordings had to conform to ''very good'' or ''excellent'' recording quality criteria as previously described [22] and show a total sleep time of .4 h. Sleep-wake state and arousals were scored using conventional criteria [23,24] and respiratory events were scored according to the Chicago criteria [25]. Standard measures of sleep structure, respiratory disturbance and oxygenation were derived as previously described [4,22] for correlation with tissue findings.…”
Section: Polysomnographymentioning
confidence: 99%
“…1 Meanwhile, there is growing evidence linking sleep disturbances with adverse pregnancy outcomes. [2][3][4] The message is clear: good sleep is important for a healthy pregnancy.…”
mentioning
confidence: 99%